Surface alloying characteristics of WS2/Cu composite electrodes deposited on an aluminum alloy by electrical discharge coating. Issue 1 (2nd January 2023) - ShanmugaElango, K.; Senthilkumar, C.
Abstract: Electrical discharge machining (EDM) is a widely used non machining technique for machining difficult-to-machine materials. Electro discharge coating (EDC) has been utilized to convert the surface of workpieces using standard electro discharge equipment by transferring electrode material to the workpiece using reverse polarity. Nowadays there is an increasing demand for lightweight materials such as aluminum (Al) alloys are widely used in aerospace as well as in automobile components due to reduction in weight to improve performance and efficiency. Nevertheless, the surface qualities such as hardness and wear resistance, of aluminium alloy are insufficient to meet the needs of a wide range of applications. As a result, the current research looked into the EDC of aluminium alloy utilizing a green compact WS2 /Cu electrode to alter the surface properties. Experiments were designed utilizing a response surface approach and a central composite rotatable design. The following significant EDC variables current, pulse on time, and pulse off time, determine the coating characteristics such as deposition rate (DR) and electrode wear rate (EWR). The most significant variables were determined using analysis of variance. A scanning electron microscope was used to explore various surface morphology that occurred during EDC. Energy-dispersive spectroscopy measurements were taken to validate the successful deposition of several elements on the workpiece surface.